امتزاز النيكل (II) من المحاليل المائية على الزيوليت الطبيعي - راهب إبراهيم; سليمان سميرة; فياض مجد (Latakia University Journal -Basic Sciences Series, 2014)
استخدم في هذا البحث الخام الزيوليتي الطبيعي السوري من منطقة أم أذن كمادة مازة لأيونات النيكل (II) من المحاليل المائية. درست عملية إزالة أيونات النيكل (II) عند شروط مختلفة وتبين أن عملية الإزالة تزداد بازدياد التركيز الابتدائي لأيونات النيكل (II) ودرجة الحرارة وقيمة PH الوسط . جميع التجارب أجريت عند زمن تماس يساوي 6 ساعات . تزداد قيمة الامتزاز من 16.36mg Ni/g من أجل التركيز الابتدائي 100mgNi/L لأيونات النيكل (II) إلى 71.33mgNi/g من أجل 1000mgNi/L =C0 . تبين أن النتائج التجريبية لعملية الامتزاز تتوافق مع منحني امتزاز لانغموير متساوي الدرجة . وبلغت السعة العظمى للامتزاز qmax=142.85mgNi/g . تتغير كمية الامتزاز عند الدرجة 298K من 16.36mgNi/g من أجل C0=100mgNi/l إلى 47.93mgNi/g من أجل C0=400mgNi/l , ثم تتغير هذه القيمة بشكل طفيف عند الدرجة 333K لتصبح 16.65mg Ni/g من أجل C0=100mgNi/g و51mgNi/g من أجل C0=400mgNi/L . تزداد كمية امتزاز أيونات النيكل (II) بازدياد قيمة PH حتى حوالي القيمة 5 ثم تبقى ثابتة حتى حوالي القيمة 6 .وبعد هذه القيمة تحدث عملية ترسيب Ni(II) على شكل هيدروكسيد. The Syrian natural zeolite from om’ozon area has been studied as adsorbent for Ni(II) ions from aqueous solution. The removal of Ni(II) ions under different conditions was studied adsorption of Ni(II) enhanced with an increase of initial concentration, temperature and PH .all experiments were carried out at contact time 6h. The amount of Ni(II) adsorption was increased from 16.36 mgNi/g for initial solution concentration of 100mg Ni/l to 71.33 mgNi/g (for C0=1000mgNi/L). The experimental data fitted well to Langmuir isotherm . The maximum capacity was qmax=142.85mgNi/g Adsorption amount at 298K varies from 16.36mgNi/g for initial solution concentration of 100mg Ni/l to 47.93mg Ni/g(for C0=400mgNi/L) and it increases at 333K to 16.65 mgNi/g and 51mgNi/g (for C0=100 and 400 mg Ni/L )respectively. The adsorption of Ni(II) ions was increased by increasing PH up to 5 and then stabilized up to PH=6 and after that the precipitation process was accured.